(untitled) (Al-Farooq Journal of Sciences, 2026)
Societies differ from one another in that they have a cultural system from which a special culture has emerged that distinguishes them from other societies. These societies do their utmost to preserve this identity, which represents a civilizational depth that constitutes the historical value of societies and culture. However, as a result of the profound changes that our society is exposed to, it becomes difficult to preserve the national cultural identity in light of the sweeping influence of globalization on our Arab society in general, and Libyan society in particular. Therefore, the research aims to know the extent of the impact of globalization on the cultural identity in society through its various mechanisms, especially the various media.